Self-Catalyzed Surface Reaction-Induced Fluorescence Resonance Energy Transfer on Cysteine-Stabilized MnO2 Quantum Dots for Selective Detection of Dopamine - Ma, Zhangyan; Xu, Yifan; Li, Peipei; Cheng, Dan; Zhu, Xiaohua; Liu, Meiling; Zhang, Youyu; Liu, Yang; Yao, Shouzhuo (Analytical chemistry (Washington), 2021)
A simple one-step ultrasonic method was developed for the synthesis of luminescent MnO2 quantum dots (MnO2 QDs) in the presence of cysteine, in which cysteine acted as the exfoliating agent and stabilization ligand. The cysteine-stabilized MnO2 QDs (Cys-MnO2 QDs) possess a fluorescence quantum yield of 4.7%, and the fluorescence intensity of Cys-MnO2 QDs is sensitive to dopamine (DA). The mechanism by which the Cys-MnO2 QDs catalyzed the self-polymerization of DA to form polydopamine nanoparticles (PDA NPs) and caused the fluorescence resonance energy transfer (FRET) between MnO2 QDs and PDA NPs was revealed. The sensing platform displayed a wide detection range (0.1–200 μM) with a low detection limit of 28 nM for the detection of DA. Moreover, the Michael addition/Schiff base reaction between the PDA NPs and cysteine on MnO2 QDs was demonstrated to facilitate the excellent selectivity toward DA detection in the presence of various interferences. This work not only develops a robust method for the preparation of highly luminescent MnO2 QDs but also provides a universal strategy on the basis of surface chemical reaction-induced FRET for the detection of DA with high sensitivity and selectivity, which is promising in the application of clinical diagnosis, drug delivery, and fluorescence-guided cancer therapy.